Perbandingan Pendapatan Pengolahan Nira Aren Menjadi Gula Aren Dan Cap Tikus Di Desa Wanga Kecamatan Motoling Timur Kabupaten Minahasa Selatan - Timporok , Amey Sutrika Meylita; Timban, Jean Fanny Junita; Memah, Melsje Yellie (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to analyze the income comparison between two types of aren sap processing businesses: palm sugar and cap tikus in Wanga Village, Motoling Timur District, South Minahasa Regency. The research employed a descriptive quantitative method with a case study approach. Data were collected through surveys, interviews, and field observations involving ten respondents five engaged in palm sugar production and five in cap tikus processing. The analysis results show that the average weekly net income from cap tikus production reached IDR 2,954,406 with a production cost of IDR 1,893,594 and revenue of IDR 4,848,000. Meanwhile, the palm sugar business generated a net income of IDR 522,134 with a production cost of IDR 1,493,866 and revenue of IDR 2,016,000. Net income per liter of aren sap was IDR 3,045.78 for cap tikus and IDR 621.59 for palm sugar. Thus, cap tikus production is economically more profitable than palm sugar. The study recommends business assistance, improved market access, and legal policy support to foster sustainable development of aren sap-based enterprises.